Perbedaan Stres Akademik Ditinjau dari Tahun Studi - Safitri, Leni; Nurfarhanah, Nurfarhanah (Lembaga Yasin AlSys, 2024)
Students often face various academic challenges that can cause stress. Higher education, as an educational institution, has a major role in developing human resources and increasing the nation's competitiveness, so the educational curriculum becomes very demanding which causes stress in students referred to as academic stress. One of the factors that influence academic stress is the year of study. The objectives of this research are 1) To describe the academic stress of first-year students; 2) To describe the academic stress of final year students; 3) To examine whether there is a difference in academic stress between first year students and final year students. This research method is quantitative with comparative descriptive research type. The population in this study were 300 students with a sample of 172 students selected by proportional random sampling method. Data collection in this study used academic stress instruments with a likert scale of 45 items that had been tested for validity and reliability, namely 0.926. Data were processed using percentage analysis techniques and comparative analysis techniques with the independent sample t-test formula. The results of this study indicate that (1) Academic stress of first-year students is in the moderate category (56.41%); (2) Academic stress of final-year students is in the moderate category (57.17%); (3) There is no significant difference between the differences in academic stress of first-year students and final-year students, with a t value of 0.555 with a significance level of 0.679>0.05. Based on the results of this study, counselors can provide assistance to students through information services, individual counseling services, group guidance services, group counseling services.